Transferencia del conocimiento, una estrategia para el control de riesgos laborales: Revisión bibliográfica (2022)
This article contains a bibliographic review in relation to the transfer of knowledge, highlighting the importance of preserving the intellectual capital of human talent, together with the objective of providing safe and healthy work environments for employees, who constitute the fundamental actors that activate the processes administrative and operational towards the continuous construction of knowledges and experiences in the context of the organization. the achievement of objectives in organizations. From these bibliographical references, an analysis and discussion about the positions of the authors is carried out, to present in a convincing way the value that adds the transfer of knowledge to the control of occupational risks, with sustainable results and permanence in time , which It will contribute to the minimization of human and material losses, and will represent an important level of effectiveness in the processes of safety and health at work.